2011
DOI: 10.1021/je200478p
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Extraction Systems of Benzoic Acid in Water and Heptane, Methylbenzene, or Trichloroethylene as Cosolvent

Abstract: Equilibrium data at (293 ( 2) K are presented for benzoic acid in water and three different organic phases (heptane, methylbenzene, and trichloroethylene). The monomeric partition constant, K P MON , and the dimerization constant, K D , for the organic phase were determined at 293 K. For the heptane/water benzoic acid system, K P MON equals (0.209 ( 0.049) m 3 AQ 3 m À3 ORG , and K D equals (1.33 ( 0.68) m 3 3 mol À1 . For the methylbenzene/water benzoic acid system, K P MON equals (1.17 ( 0.92) m 3 AQ 3 m À3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A two-phase system of water and n-heptane was selected to study the volume fraction. , For all experiments, demineralized water was used. Pelikan Royal Blue ink was obtained from BETO Schoolartikelen.…”
Section: Methodsmentioning
confidence: 99%
“…A two-phase system of water and n-heptane was selected to study the volume fraction. , For all experiments, demineralized water was used. Pelikan Royal Blue ink was obtained from BETO Schoolartikelen.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the contribution rates of enthalpy and entropy of dissolution to the Gibbs energy of dissolution were estimated by using %ξ H and %ξ TS . The equations for %ξ H and %ξ TS are as follows , % ξ H = false| Δ sol H ° false| false| Δ sol H ° false| + | T normalΔ sol S ° | × 100 % ξ TS = false| T Δ sol S ° false| false| Δ sol H ° false| + | T normalΔ sol S ° | × 100 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the contribution rates of enthalpy and entropy of dissolution to the Gibbs energy of dissolution were estimated by using %ξ H and %ξ TS . The equations for %ξ H and %ξ TS are as follows 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…Visscher et al indicated that the extraction of benzoic acid from water using n-hexane was a chemical reaction process, where benzoic acid in the organic phase and aqueous phase undergo mutual transfer [10]. Benzoic acid would ionized in water while reacting to form dimerized benzoic acid in the organic phase.…”
Section: Experimental Principlementioning
confidence: 99%
“…Its mass transfer and separation properties could be intensified simultaneously and it particularly suitable for O/W emulsion systems. Benzoic acid was applied as a solute because it could be measured in-line in both phases by UVvis spectroscopy [10]. Additionally, it had low toxicity, and it is inexpensive.…”
Section: Introductionmentioning
confidence: 99%